Determinants of resilience for food and nutrition security in South Sudan - Ulimwengu, John M.; Thomas, Timothy S.; Marivoet, Wim; Benin, Samuel (International Food Policy Research Institute, 2022)
The paper analyzes the determinants of long-term individual and community resilience for food and nutrition security in South Sudan using data from multiple sources including key informant interviews, household and community surveys, and georeferenced secondary data on climate, agricultural production, irrigation, and market access. Major agricultural development constraints as well as incidence of and responses to shocks and conflict are described. Climate-crop modeling and simulation methods are used to evaluate the constraints and to identify crop investment options. Then, a spatial typology of food and nutrition security is used to evaluate the constraints along the production-to-nutrition pathway to identify interventions that target different segments of the chain and options for improving agriculture and broader development outcomes. These are classified into production, access, and utilization efficiencies, and whether the underlying constraints are structural (i.e., level of efficiency remains the same over time) or stochastic (i.e., level of efficiency changes over time). The analysis is focused on about a dozen selected counties. The results show that development challenges are being compounded by climate change, with significant increases in the mean annual rainfall and daily maximum temperature for the warmest month. Between 1975 and 2016 for example, the mean annual rainfall in the selected counties increased by 40-111 mm/year, with a rise in the intensity of 0.2-1.3 mm per event. The daily maximum temperature for the warmest month increased by 2.0-3.2°C. If these trends (especially for temperature) continue to 2050, crop yields are projected to decline in the selected counties on average by 12-23% for sorghum, 9-18% for maize, 19-30% for groundnuts, and 16-24% for cassava. In general, there is an inverse-U-shaped the relationship between temperature and yields. While the peak of the inverse U varies by crop, time of the growing season, and other factors, crops in South Sudan are typically on the downward sloping side of the inverse U implying that increases in temperature will decrease yields (and at an increasing rate). Results of a spatial typology show that a majority (78%) of the selected counties are classified as having medium production efficiency and 22% as low production efficiency, none with high production efficiency. With respect to access to nutritious food, 55%, 29%, and 17% of the counties are classified as low, medium, and high access efficiency, respectively. And regarding the conversion of food access into nutritional status, 37%, 26%, and 37% are classified as low, medium, and high utilization efficiency, respectively. Whereas production efficiency mostly remains constant over time, (with only 24% of the counties recording substantial changes in efficiency level), access and utilization efficiency appear more volatile (with substantial changes observed in 52% of the counties). These results suggest that the access segment of the production-to-nutrition value chain is the most constraining, followed by the utilization segment. The differences in the results across counties reflect differences in development constraints across the country, which are also described. Implications of the results for building long-term individual and community resilience are discussed, in addition to areas for further research. Given the complex nature of crises facing South Sudan, our findings call for a comprehensive policy approach to address not only the urgent humanitarian crisis but also to help restore agricultural production systems as well as support communities to cope, recover, and build their vii resilience to shocks and crises. This is in line with the Partnership for Recovery and Resilience (PfRR) integrated programme framework for resilience which comprises four pillars: i) re-establish access to basic services, ii) rebuild trust in people and institutions, iii) restore productive capacities, and iv) nurture effective partnerships.